Synthesis, NMR and X-ray studies on novel heteroaromatic aldoxime O-ether 2- and 2, 3-unsaturated glycosides. Issue 35 (27th August 2020) - Lafuente, Leticia; Rojas, Agustín H.; Piro, Oscar E.; Echeverría, Gustavo A.; Ponzinibbio, Agustín
Graphical abstract: Highlights: Hydrolytically stable glycosidic bond was designed and performed between 2-deoxy sugars and heterocycles. Heteroaromatic aldoxime O-ether 2- and 2, 3-unsaturated glycosides were fully characterized by NMR and X-ray analysis. Carbohydrate-derived oxime ethers were synthesized in good yields and high anomeric and E/Z selectivity. Abstract: We present the synthesis of novel hydrolytically stable heteroaromatic oxime ether glycosides in very good yields and high anomeric selectivity. The products obtained are α-glycosides and the double bond configuration is E . The aldoxime O- ether carbohydrate derivatives were analysed by structural X-ray diffraction and NMR spectral data. A complete investigation on the glycoside structures, that includes conformation characteristics in the pyranose ring and heterocyclic alternative positions, is also described.